AN INVESTIGATION INTO COGNITIVE EXPRESSIONS CONTAINING “HEAVEN” IN ENGLISH AND VIETNAMESE SONGS - Nguyễn Ăyun Thùy My (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
My study examines the cognitive expression containing the word “heaven” in English and Vietnamese songs. In addition, the research analysis throughout the whole songs which plays an important role in understanding the meaning of songs that the author want to say to. The concept of “heaven” is also considered as one of the abstract entity having close relations with cognition. Therefore, this paper attempts to conduct a contrastive analysis research of cognitive expressions of “heaven” in English and Vietnamese. This paper chooses the quantitative and qualitative approaches throughout the study to achieve the purpose. The source of data will be taken from 266 songs composed by English and Vietnamese composers.The data can be restricted to the scope of analyzing the cognitive expressions containing “heaven” songs, not in other forms of art such as poetry, literature or films. And there are approximately 298 cognitive expressions of “heaven” collected from American and Vietnamese songs. The findings presented eighteen target domains which occur in cognitive expressions of “heaven” in American, Vietnamese, or both. To achieve the research aims and objectives the study tries to answer two questions that are how do the cognitive expressions containing “heaven” relate to the image of “heaven” in English and Vietnamese songs? and what are the similarities and differences of cognitive expressions containing “heaven” in English and Vietnamese songs? However, fifteen cognitive expressions containing the word “heaven” occurs in English while there remains some cognitive expressions of “heaven” that occur in Vietnamese but not in English. Based on the findings of the thesis, some implications for teaching, learning and translating of conceptual metaphors will be suggested. Furthermore, this thesis is useful for Vietnamese learners of English to be successful in cross - cultural communication.